Omaezallene from Red Alga Laurencia sp.: Structure Elucidation, Total Synthesis, and Antifouling Activity1. Issue 15 (11th March 2014) - Umezawa, Taiki; Oguri, Yuko; Matsuura, Hiroshi; Yamazaki, Shohei; Suzuki, Masahiro; Yoshimura, Erina; Furuta, Takeshi; Nogata, Yasuyuki; Serisawa, Yukihiko; Matsuyama‐Serisawa, Kazuyo; Abe, Tsuyoshi; Matsuda, Fuyuhiko; et al.
Abstract Natural antifouling products have been the subject of considerable attention. We screened marine algae for antifouling activity and discovered omaezallenes, the new bromoallene‐containing natural products isolated from the red alga Laurencia sp. Described is the isolation, structure elucidation, and total syntheses of omaezallenes. The relative and absolute configurations of natural omaezallenes were unambiguously established through total synthesis. The antifouling activities and ecotoxicity of omaezallenes were also evaluated.